Social Media in Bosnia and Herzegovina - StojanoviÄ‡, Zvezdan (International Journal of Engineering and Technology, 2018)
The use of social media has a wide range of applications in different areas of life. Accordingly, the impact of social networks in everyday life is growing. Bosnia and Herzegovina has a solid telecommunication infrastructure, which is of great importance for the development of social networks. This paper will show the application of social networks in areas such as tourism, education, marketing, politics and local and state administration bodies in Bosnia and Herzegovina.Â Â